A Novel Detachable, Reusable, and Versatile Acoustic Tweezer Manipulation Platform for Biochemical Analysis and Detection Systems - Yukai Liu; Miaomiao Ji; Yichi Zhang; Xiaojun Qiao; Nanxin Yu; Chenxi Ding; Lingxiao Yang; Rui Feng; Xiujian Chou; Wenping Geng (Biosensors, 2022)
Multifunctional, integrated, and reusable operating platforms are highly sought after in biochemical analysis and detection systems. In this study, we demonstrated a novel detachable, reusable acoustic tweezer manipulation platform that is flexible and versatile. The free interchangeability of different detachable microchannel devices on the acoustic tweezer platform was achieved by adding a waveguide layer (glass) and a coupling layer (polydimethylsiloxane (PDMS) polymer film). We designed and demonstrated the detachable multifunctional acoustic tweezer platform with three cell manipulation capabilities. In Demo I, the detachable acoustic tweezer platform is demonstrated to have the capability for parallel processing and enrichment of the sample. In Demo II, the detachable acoustic tweezer platform with capability for precise cell alignment is demonstrated. In Demo III, it was demonstrated that the detachable acoustic tweezer platform has the capability for the separation and purification of cells. Through experiments, our acoustic tweezer platform has good acoustic retention ability, reusability, and stability. More capabilities can be expanded in the future. It provides a simple, economical, and multifunctional reusable operating platform solution for biochemical analysis and detection systems.